The forbidden door - Norweb, Jeanne K. (D.C. Cook Pub. Co. ; Grastorf, Lang, 1985)
When David and Laura set out to explore a seaside cover near their grafather's home expecting to find only seashells and tide pools, they happen upon a wooden door built into the rocks and discover on the other side a mysterious world where the sides of good and evil are clearly drawn.